High-quality linear interpolation for demosaicing of Bayer-patterned color images - Malvar, Henrique S.; He, Li-wei; Cutler, Ross (International Conference of Acoustic, Speech and Signal Processing, 2004)
This paper introduces a new interpolation technique for demosaicing of color images produced by single-CCD digital cameras. We show that the proposed simple linear filter can lead to an improvement in PSNR of over 5.5 dB when compared to bilinear demosaicing, and about 0.7 dB improvement in R and B interpolation when compared to a recently introduced linear interpolator. The proposed filter also outperforms most nonlinear demosaicing algorithms, without the artifacts due to nonlinear processing, and a much reduced computational complexity.